Study of reaction conditions and substrate for the development of flexible antennas by the electroless method - Dalló, Luíse Cambruzzi; Lamberty, Paola; Mezzeti, Gabriela; Santin, Cristiane Krause; Fernandes, Iara Janaína; Peter, Celso (Revista Liberato, 2020)
The method of surface coating, known as electroless, is based on the deposition of metals without the presence of an electric current, being an alternative for the deposition of metals using direct printing, thus avoiding the need to use photoresist to standardize the metal layer. The present work aims to study substrates, based on polyethylene terephthalate (PET), and their covering using the electroless technique. In this study, factors such as plasma, temperature and immersion time were investigated, when covering the surface, using a silver nitrate solution and a copper bath. The results showed that these factors interfere in obtaining a homogeneous coating with efficient conductivity. In addition, it is concluded that the electroless technique is a low-cost, fast and efficient method for coating flexible surfaces with metallic materials, being, therefore, very promising.